Treasure Island - Stevenson, Robert Louis, 1850-1894.; McNaughton, Colin (New York : Holt, 1993)
While going through the possessions of a deceased guest who owed them money, the mistress of the inn and her son find a treasure map that leads them to a pirate's fortune.
"First published in 1883"--verso T.p.
"This edition first published in the United Kingdom by Pan McMillan Children's Books"--verso T.p.
Keywords: Buried treasure -- Fiction; Pirates -- Fiction; Adventure and adventurers -- Fiction